Functional analysis of the F337C mutation in the CLCN1 gene associated with dominant myotonia congenita reveals an alteration of the macroscopic conductance and voltage dependence. Issue 2 (28th January 2021) - Jehasse, Kevin; Jacquerie, Kathleen; de Froidmont, Alice; Lemoine, Camille; Grisar, Thierry; Stouffs, Katrien; Lakaye, Bernard; Seutin, Vincent
ABSTRACT: Background: Myotonia congenita (MC) is a common channelopathy affecting skeletal muscle and which is due to pathogenic variants within the CLCN1 gene. Various alterations in the function of the channel have been reported and we here illustrate a novel one. Methods: A patient presenting the symptoms of myotonia congenita was shown to bear a new heterozygous missense variant in exon 9 of the CLCN1 gene (c.1010 T > G, p.(Phe337Cys)). Confocal imaging and patch clamp recordings of transiently transfected HEK293 cells were used to functionally analyze the effect of this variant on channel properties. Results: Confocal imaging showed that the F337C mutant incorporated as well as the WT channel into the plasma membrane. However, in patch clamp, we observed a smaller conductance for F337C at −80 mV. We also found a marked reduction of the fast gating component in the mutant channels, as well as an overall reduced voltage dependence. Conclusion: To our knowledge, this is the first report of a mixed alteration in the biophysical properties of hClC‐1 consisting of a reduced conductance at resting potential and an almost abolished voltage dependence. Abstract : We describe a rare variant of the CLCN1 gene which was found in one family. Functional analysis demonstrated that the channel inserts normally into the membrane, but has a low conductance at −80 mV and a severely reduced voltage‐dependence.